Mid‐ to long‐term clinical and echocardiographic outcomes after transcatheter aortic valve replacement with a new‐generation, self‐expandable system. Issue 1 (23rd May 2020) - Siqueira, Dimytri A.; Simonato, Matheus; Ramos, Auristela A.; Bignoto, Tiago; Le Bihan, David; Barreto, Rodrigo B. M.; Senra, Tiago; Pinto, Ibraim M.; Kambara, Antonio M.; Santos, Magaly A.; Viana, Renata; Sousa, Amanda G. M. R.; et al.
Abstract: Objectives: The aim of the study was to evaluate mid‐ to late clinical and echocardiographic outcomes after transcatheter aortic valve replacement (TAVR) with Acurate neo ™ (Boston Scientific, Boston, MA). Background: TAVR is an established treatment for aortic stenosis (AS). Few data exist on mid‐ to long‐term outcomes and durability after new‐generation valves. Methods: All consecutive patients ( n = 104) who underwent Acurate neo ™ implantation from 2012 to 2018 were included. Follow‐up was systematically performed at 1, 6, 12, and 24 months and yearly thereafter. Outcomes were reported according to VARC‐2, and structural valve deterioration (SVD) or bioprosthetic valve failure defined accordingly to new definitions. Results: Mean age was 82 ± 5.4 years, 56.7% were female and the Society of Thoracic Surgeons score for mortality was 5.9 ± 4%. Patients were followed for a median of 3 years (1, 092 days; IQR 1.5–4 years), and the maximum follow‐up was 7 years. All‐cause mortality values at 1 and 5 years were 8.5% and 40.5%, respectively. No relevant changes in mean gradient and orifice area occurred (7.9 ± 3.8 mmHg and 1.9 ± 0.3 cm 2 at 1 year; 6.6 ± 2.1 mmHg and 1.8 ± 0.3 cm 2 at 5 years), and there was a significant rate of paravalvular leaks resolution at 1, 2, and 3 years ( p = .004; p  < .001; p  < .001, respectively). None of the patients had leaflet thrombosis or endocarditis. One patient developed SVD at 84 months. Conclusions: Acurate neo ™ was associated with sustained echocardiographic results. Reassuring mid‐ to long‐term outcomes was observed in this cohort of elderly patients with severe AS.